Carbohydrate quantity is more closely associated with glycaemic control than weight in pregnant women with type 1 diabetes: Insights from the Diabetes and Pre‐eclampsia Intervention Trial (DAPIT). Issue 6 (14th June 2022) - Hill, Alyson J.; Patterson, C. C.; Young, I. S.; Holmes, V. A.; McCance, D. R.
Abstract: Background: The present study aimed to explore the relationships between carbohydrate intake, body mass index (BMI) and glycaemic control (HbA1c) in pregnant women with type 1 diabetes mellitus (T1DM) Methods: Secondary analysis of data was undertaken to assess dietary intake in a cohort of women who participated in a randomised controlled trial (RCT) of antioxidant supplementation to prevent preeclampsia (DAPIT 10 ). Study‐specific peripheral venous blood samples were obtained for HbA1c at 26 and 34 weeks. Diet was collected using a validated semiquantitative food frequency questionnaire at 26–28 weeks of gestation which assessed dietary intake over 2 weeks. Mean daily average nutrient intakes were analysed using Q Builder nutritional software and SPSS, version 25. Results: Dietary data were available for 547 pregnant women (72% of cohort) aged 29 years (95% confidence interval [CI] = 28.9–29.9) with average diabetes duration 11.8 years (95% confidence interval = 11.1–12.6). Average body mass index (BMI) (<16 weeks of gestation) was 26.7 kg/m 2 (95% CI = 26.3 −27, range 18.8–45.6 kg/m 2 ); 43% ( n = 234) were overweight (BMI = 25.0−29.9 kg/m 2 ) and 20% ( n = 112) were obese (BMI ≥ 30 kg/m 2 ). Differences in HbA1c and carbohydrate quantity and quality were found when adjusted for age and insulin dose. No differences between BMI group were observed for total carbohydrate and glycaemic control; however, differences were noted in fibre and glycaemic index. Conclusions: Average quantity of dietary carbohydrate influenced HbA1c when adjusted for insulin dose however, BMI had less impact. More research is required on the relationship between carbohydrate consumption and glycaemic control in pregnancy. Abstract : Carbohydrate quantity but not body mass index (BMI) is associated with glycaemic control in pregnant women with type 1 diabetes mellitus (T1DM). Key points: A positive association between glycaemic control (HbA1c) and higher quantity of carbohydrate (>264 g of carbohydrate) consumed in late pregnancy (mean gestational age 27.9 weeks) ( p = 0.002) was shown in the present study. Sixty‐three percent of women were classified as overweight or obese in early pregnancy, and almost 70% gained above the Institute of Medicine recommendations for optimal gestational weight gain. However, no association between body mass index or gestational weight gain and glycaemic control was found. This present study suggests that monitoring quantity and type of carbohydrate consumed (and matching insulin doses) may have an impact on glycaemic control and is more closely associated than weight.